Tracing the invasion: Wing morphometrics reveal population spread and adaptation patterns of Halyomorpha halys (Stål, 1855) across Southern Europe. - Martina Pajač Beus; Darija Lemic; Hugo A Benítez; Laura M Pérez; Mojca Rot; Aleksandra Konjević; Stefanos S Andreadis; Ivana Pajač Živković (PLoS ONE)
Invasive species such as Halyomorpha halys (Stål, 1855), the brown marmorated stink bug, pose a significant threat to agriculture due to their rapid spread and adaptability. The aim of this study is to assess the phenotypic variability of H. halys populations by analyzing the size and shape morphology of the anterior and posterior wings and to determine whether geometric morphometrics can serve as a cost-effective alternative to genetic methods for tracking invasion patterns. Populations from four southern European countries (Croatia, Serbia, Slovenia and Greece) with 540 specimens and 2,160 wings were analysed and showed clear phenotypic differences in wing morphology consistent with the known invasion dynamics previously determined by genetic studies. Mahalanobis distances highlight the close morphological relationship between the Serbian and Slovenian populations, suggesting common ancestry or recent gene flow, while the Greek and Croatian populations show significant differences, suggesting different invasion pathways or rapid morphological adaptation. The Greek population exhibited lower phenotypic plasticity, whereas the Serbian population displayed the greatest variation, likely reflecting the influence of multiple invasion sources. These results show that wing morphology can reliably detect invasion-related patterns and phenotypic plasticity and is a valuable tool for biomonitoring in integrated pest management programs, especially in areas where genetic methods are less feasible. This study highlights the utility of geometric morphometrics in monitoring the spread and adaptation of invasive species such as H. halys in different environments.